Pathological alterations and COHb evaluations as tools for investigating fire-related deaths in veterinary forensic pathology - Piegari, Giuseppe; d’Aquino, Ilaria; Salanti, Giovanni Valerio; Russo, Valeria; De Biase, Davide; Caccia, Giulia; Carfora, Anna; Campobasso, Carlo Pietro; Paciello, Orlando (Frontiers in Veterinary Science, 2024)
Fire-related deaths are usually a consequence of carbon monoxide (CO) poisoning or shock from thermal injuries. In humans, high levels of carboxyhemoglobin (COHb) concentrations in the blood can support a diagnosis of CO poisoning. In veterinary medicine, few studies investigated the pathological changes and blood COHb% in fire victims, and no data are available on post-mortem changes in blood gas composition due to fire. This study aims to investigate the pathological changes and COHb levels in both animal victims of fire and cadavers experimentally exposed to fire. For this purpose, dogs were selected and subdivided into three groups. Group A comprised 9 adult dogs, and Group B comprised 7 puppies that died under fire-related conditions. Group C was represented by 4 dog cadavers experimentally exposed to heat and smoke. A complete macroscopic, histological, and COHb evaluation were performed on each animal. Animals in Groups A and B showed cherry-red discoloration, thermal-injuries and soot deposits along the respiratory tract. Animals in Group C showed thermal injuries and soot deposits limited to the upper respiratory tract. The mean COHb% values in cadavers in Group C were lower than those observed in the other groups but higher compared to the values detected before the heat and smoke treatment. These findings suggest that both pathological changes and COHb analysis are valid tools for investigating fire-related deaths in dogs. However, the increase of COHb levels in cadavers exposed post-mortem to heat and smoke highlights how the COHb analysis should always be evaluated together with macroscopical and microscopical findings to avoid significant misjudgments in investigating fire-related fatalities in veterinary forensic practice.